2021
DOI: 10.1186/s12935-020-01690-1
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOXA-AS2 promotes glioblastoma carcinogenesis by targeting miR-885-5p/RBBP4 axis

Abstract: Background LncRNA HOXA-AS2 has been found in the literature to deteriorate glioblastoma. However, its regulatory mechanism is yet to be fully investigated. Our study focused chiefly on the interaction and role of the HOXA-AS2/miR-885-5p/RBBP4 axis in the development of glioblastoma. Methods qRT-PCR analysis was performed to detect the expression of lncRNA, miRNA and mRNA in glioblastoma tissues and cells. Dual-luciferase assay, RIP assay and RNA pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Recent research emphasizes that epigenomic factors play a crucial role in the development of PD, and it is assumed that the initiation of PD is promoted by a combination of a genetic predisposition and environmental triggers [ 35 , 36 ]. Although several studies have demonstrated that HOXA-AS2 promotes tumor proliferation by serving as an “miRNA sponge” [ 30 , 37 , 38 ], it has also been shown to enhance gastric cancer proliferation by epigenetically silencing the expression of p21, plk3, and DDIT3 [ 39 , 40 ]. A study highlighted the role of aberrant DNA methylation of the HOXA gene cluster in the pathogenesis of Alzheimer’s disease [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research emphasizes that epigenomic factors play a crucial role in the development of PD, and it is assumed that the initiation of PD is promoted by a combination of a genetic predisposition and environmental triggers [ 35 , 36 ]. Although several studies have demonstrated that HOXA-AS2 promotes tumor proliferation by serving as an “miRNA sponge” [ 30 , 37 , 38 ], it has also been shown to enhance gastric cancer proliferation by epigenetically silencing the expression of p21, plk3, and DDIT3 [ 39 , 40 ]. A study highlighted the role of aberrant DNA methylation of the HOXA gene cluster in the pathogenesis of Alzheimer’s disease [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the BrdU Cell Proliferation Assay Kit (Cat#: 6813, CST, MA, USA) was used to detect cell proliferation. BrdU (10 μM) was added to the plate and incubated for 4 h and then incubated with secondary antibody for another 1 h. The OD value was examined using a multimode plate reader at a wavelength of 450 nm [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Liao et al demonstrated that lncRNA MALAT1 facilitates the malignancy of GBM via the miR-199a/ZHX1 axis [ 14 ]. Shou et al revealed that lncRNA HOXA-AS2 is upregulated in GBM and promotes cancer development via regulating the miR-885-5p/RBBP4 axis [ 15 ]. MiR-34a expression is downregulated in GBM tissues and inhibits GBM progression [ 16 ].…”
Section: Introductionmentioning
confidence: 99%